Role of Ultrasound as an Adjunct Modality to Mammography in the Diagnostic Evaluation of Breast Cancer - Tehmina Sajjad Khan (Journal of Rawalpindi Medical College, 2016)
Background: To determine the role of ultrasound as an adjunct modality to mammography in diagnosing breast cancer. Methods: Total 100 patients of breast cancer were recruited in this comparative study. These cases were subjected to mammography. Ultrasound was then performed as an adjunct modality while clinical and mammographic results were available to the radiologist evaluating the ultrasound scans. Patients with positive findings were then followed for histopathology findings obtained from excisional biopsy or mastectomy specimen. The results of histopathology were taken as gold standard. Sensitivity and specificity of mammography and adjunctive ultrasound was calculated by constructing a 2 x 2 table taking histopathology as gold standard. Statistical measures of accuracy, sensitivity, specificity, positive predictive (PPV) and negative predictive values (NPV) were calculated. Results: Age distribution revealed, 68 patients (68.0%) were < 40 years of age. Mean age of the patients was 44.9 ±5.2 years. Distribution of cases by presenting symptoms was as follows: breast lump 93 (93.0%), and breast pain 7 (7.0%) with nipple discharge 10 (10.0%) and nipple retraction 8 (8.0%). Family history of breast cancer was present in 37.0%. Combined sensitivity of mammography and adjunctive ultrasound was 94.67%, specificity 77.78%, diagnostic accuracy 85.54%, positive predictive value 89.87%, negative predictive value 63.63% comparatively better than these modalities alone. Conclusion: Ultrasound can be considered as a primary screening tool in younger population and as an adjunct to mammography in elder women to minimize the chances of missing diagnosis of breast cancers.